ASSESSMENT OF ENVIRONMENTAL IMPLICATIONS OF ELECTRIC VEHICLES: A REVIEW - Prantik Dutta (Yeshwantrao Chavan College of Engineering, India, 2021)
The emergence of hybrid electric vehicles (HEVs) has paved a way for the automobile industry to tap into the vast potential of renewable sources of energy and to look for eco friendly alternatives to fossil fuels. Not only can the depletion of non renewable resources be countered effectively but the harmful detrimental effects of using these fossil fuels can also be reduced. Even though it has been established that HEVs tend to have more eco friendly benefits than their internal combustion engine vehicles (ICEV) counterparts, they too are not immune to adverse environmental implications. The production, operation and end of life phases of HEVs contribute to major adverse environmental effects related to greenhouse gases (GHG) emissions, human toxic by-products etc. Hence an assessment of their environmental implications is being discussed in this paper and light has been shed on different assessment categories such as acidification potential, eutrophication, human toxicity potential, global warming potential etc. Furthermore the phases and parts of a HEV which contribute majorly to these implications are also discussed briefly. The environmental implications of the energy generation sources used in these HEVs are also taken into account.